Pengaruh Ethical Leadership Terhadap Employee Engagement dengan Self-Efficacy dan Organizational Commitment sebagai Mediasi: Studi pada Karyawan Edu-Tech Jakarta - Muhammad Alfi Hussain; Eisha Lataruva (Diponegoro Journal of Management, 2026)
The edutech startup industry in Indonesia is currently experiencing rapid growth but is also confronting significant challenges in retaining employee engagement. Company X, as a leading startup in this sector, must ensure the dedication of its employees amidst high work dynamics and pressure. This study is motivated by inconsistencies in previous literature regarding the direct influence of ethical leadership on employee engagement, as well as the need to understand the internal mechanisms that bridge this relationship, namely through employees' psychological and affective factors. This research aims to test and prove that ethical leadership positively influences employee engagement, mediated by self-efficacy (self-confidence) and organizational commitment (emotional attachment).Data collection for this study involved 80 permanent employees of Company X using a census method. The data obtained were subsequently analyzed using the Structural Equation Model (SEM) based on Partial Least Square (PLS) method.Based on the research findings, it was found that ethical leadership has a positive but insignificant effect on employee engagement, while it has a positive and significant effect on self-efficacy and organizational commitment. Furthermore, self-efficacy and organizational commitment were proven to have a positive and significant influence on employee engagement, and both successfully mediated the relationship between ethical leadership and employee engagement. This conclusion underscores that ethical leaders succeed in enhancing employee engagement through the development of self-efficacy and organizational commitment.